The Long Run : 1916 - Wharton, Edith, 1862-1937 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Long Run" by Edith Wharton is a novel written during the early 20th century. This work explores the themes of love, societal expectations, and personal choices through the lens of its protagonist, Halston Merrick, as he reflects on his relationships and the nature of life over time. The story delves into the emotional landscape of Merrick's friendship and romantic feelings towards Paulina Trant, illustrating the conflicts between duty, desire, and the passage of time. In the narrative, Merrick reconnects with Paulina at a gathering after many years apart, only to find that their lives have taken different turns filled with regret and compromise. As they navigate their past and present, Merrick grapples with his choices that led him to stay in a fulfilling yet constrained life, managing the family business rather than pursuing greater passions. He ultimately reflects on the complexity of love and societal duties as Paulina marries another man, Reardon. The unfolding dialogue unearths a blend of nostalgia, longing, and the painful recognition of how life$1 (Bs decisions can reshape one$1 (Bs identity and emotional reality over time, culminating in an exploration of what it means to genuinely live, love, and grow in "the long run." (This is an automatically generated summary.)s
Release date is 2008-01-03
Produced by David Widger
Keywords: United States -- Social life and customs -- Fiction; Man-woman relationships -- Fiction